Curious George Flies a Kite - Rey, Margret; Rey, H. A. 1898- (Hans Augusto) (Boston, Houghton Mifflin, 1958)
A little monkey needs to rescued when he tries to fly a kite.
Keywords: Monkeys -- Fiction; Kites -- Fiction